EXPLORING THE EVOLUTION AND IMPACT OF THE INTERNATIONAL SCHOOL OF FINANCIAL TECHNOLOGY AND SCIENCES (ISFT) - Saparov Aktam Jurayevich (Journals Park Publishing, 2024)
The International School of Financial Technology and Sciences (ISFT) has emerged as a pioneering institution at the intersection of finance and technology, shaping the future of financial education and practice worldwide. This article delves into the history, curriculum, impact, and future prospects of ISFT, highlighting its contributions to the field of financial technology.
Keywords: ISFT, financial education, academic programs, history and evolution, International School of Financial Technology.